Pre-service language teacher training for distance education - Luz, Emeli Borges Pereira (Texto Livre, 2018)
ABSTRACT:This research questions whether English language teaching courses offered by Brazilian public universities equip the next generation of teachers with the necessary skills to teach via distance learning through online environments. The methodology used is quantitative in nature and considers 118 universities that offer English Language and Literature courses. Their curricula were analyzed solely to investigate if the courses offered any modules related to distance learning. Only four institutions propose entire modules that deal with distance education although they are elective. In order to propose an alternative to this issue, a suite of three modules related to technology, distance teaching and learning are presented. TPACK model was used as a guide to analyze the proposed modules. The development of the modules could establish a more solid and holistic pre-service teacher education, so that pre-service teachers can be prepared to teach in online and blended environments.KEYWORDS: pre-service training; distance education; TPACK; public universities. RESUMO:Esta pesquisa questiona se os cursos de ensino de inglês oferecidos por Universidades Públicas Brasileiras equipam a próxima geração de professores com as habilidades necessárias para ensinar via educação a distância através de ambientes online. A metodologia utilizada é de natureza quantitativa e considera 118 universidades que oferecem graduação em Língua e Literatura Inglesa. Os respectivos currículos foram analisados unicamente para investigar se os cursos ofereciam módulos relacionados ao ensino a distância. Apenas quatro instituições propõem módulos inteiros que lidam com educação a distância, embora sejam eletivos. Para propor uma alternativa a essa questão, é apresentado um conjunto de três módulos relacionados à tecnologia, ensino a distância e aprendizado. O modelo TPACK foi utilizado como um guia para analisar os módulos propostos. O desenvolvimento dos módulos pode estabelecer uma formação de professores pré-serviço mais sólida e holística, para que os professores possam estar preparados para ensinar em ambientes online e híbridos.PALAVRAS-CHAVE: formação pré-serviço; educação a distância; TPACK; universidades públicas.